THE FEMALE G-SPOT: ANATOMICAL FACT OR FANTASY? - Nikola Tomov; Nikolay Dimitrov; Antoaneta Georgieva; Ivelina Ivanova; Jordan Stoyanov; Dimitar Sivrev (Science & Research)

(untitled)
Ever since its existence was suggested by Ernst Gräfenberg in the 1940s, the eponymous G-spot remains a controversial topic among anatomists, gynecologists, sexual medicine specialists, and self-proclaimed sexologists. Its assumed localization on the anterior vaginal wall, 50 to 80 mm from the introitus, has been established predominantly relying on self-report, questionnaires, and vaguely reasoned functional tests, all contributing toward the notion that a functionally important for the female orgasm zone indeed exists on the anterior vaginal wall. Despite those statements are not based on the proven fact of the presence of a discrete anatomical structure, numerous reports have speculated about possible muscular, vascular, and even neural peculiarities of the region, contributing to its functional importance. However, even though the distal anterior wall of the vagina is a highly sensitive area, included in the morphofunctional clitourethrovaginal (CUV) complex, the existence of the G-spot as a separate morphological entity is yet to be proven. The present report reviews the reports regarding the morphological essence of the G-spot and summarizes the available data on the anatomy of the anterior vaginal wall.